Fuel savings by using better-quality insulation in refrigerating vans - Jovanović, Branislav; Maljković, Miloš; Stamenković, Dragan; Popović, Vladimir (Industrija, 2021)
An additional attention must be payed to the energy efficiency of refrigerated vans transporting perishable foodstuffs, because inefficient operation of refrigeration units installed on these vehicles increases fuel consumption and exhaust gases emissions. The amount of fuel consumed by mechanical refrigeration unit drive can be reduced in many ways. This paper is analysing the impact of thermal insulation quality on the fuel consumed by mechanical refrigeration unit installed on a typical van. The results of the research show that by choosing heavy thermal insulation around € 420 can be saved annually on fuel consumed by mechanical refrigeration unit driven by vehicle’s engine while transporting deeply frozen fish at -20 °C. If the van is transporting raw meet at 0 °C annual savings can be around € 110. The analysis is done for the mean monthly temperatures in Belgrade, Serbia and the price of each type of insulation and fuel in Serbia.